2012
DOI: 10.1097/pai.0b013e318245e05b
|View full text |Cite
|
Sign up to set email alerts
|

Use of IMP3, S100P, and pVHL Immunopanel to Aid in the Interpretation of Bile Duct Biopsies With Atypical Histology or Suspicious for Malignancy

Abstract: Histologic evaluation of an endoscopic bile duct biopsy for malignancy is a known challenge. Our prior study has shown that the insulin-like growth factor-II mRNA binding protein-3 (IMP3), S100P, and the von Hippel-Lindau gene product (pVHL) are a useful immunopanel for the distinction between adenocarcinoma and benign biliary epithelium. To further evaluate the usefulness of the IMP3, S100P, and pVHL immunopanel to aid in the interpretation of bile duct biopsies, 16 histologically challenging bile duct biopsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…S100P is a member of the S100 calcium-binding protein family, initially isolated from human placenta [17]. Overexpression has been reported in several epithelial cancers including PDA, adenocarcinoma of extrahepatic bile ducts, and gallbladder adenocarcinoma [4,[6][7][8]10,18,19]. Our current findings showed positive S100P staining in 95% of PDA, which was in line with our previous observations [7,9,10].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…S100P is a member of the S100 calcium-binding protein family, initially isolated from human placenta [17]. Overexpression has been reported in several epithelial cancers including PDA, adenocarcinoma of extrahepatic bile ducts, and gallbladder adenocarcinoma [4,[6][7][8]10,18,19]. Our current findings showed positive S100P staining in 95% of PDA, which was in line with our previous observations [7,9,10].…”
Section: Discussionsupporting
confidence: 92%
“…We have recently established the diagnostic value of S100P, the von Hippel-Lindau gene product (pVHL), insulin-like growth factor-II messenger RNA-binding protein-3 (IMP3), and mammary serine protease inhibitor (maspin) for PDA, gallbladder adenocarcinoma, and adenocarcinoma of the extrahepatic bile ducts [4][5][6][7][8][9][10]. These studies demonstrated that these biomarkers constitute a useful diagnostic immunohistochemical panel for confirming the diagnosis of adenocarcinoma in difficult cases, which can be helpful in the distinction from normal or reactive epithelium of the pancreas, gallbladder, and extrahepatic bile ducts in surgical, biopsy, and fine-needle aspiration specimens.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, benign/reactive biliary epithelium frequently exhibits an IMP3-/S100P-/pVHL+ staining pattern [24,25].…”
Section: Introductionmentioning
confidence: 88%
“…167 pVHL immunostaining on bile duct biopsies can be difficult to interpret. In one of our studies, 171 reduced immunoreactivity, instead of completely negative staining, was observed in suspicious cells in one-half of malignant cases. The reduction occurs primarily on cell membranes.…”
mentioning
confidence: 99%
“…Nonneoplastic pancreaticobiliary epithelial cells are always negative. However, IMP3 does not discriminate invasive adenocarcinoma from dysplasia, 169,171,178 and thus careful histologic evaluation is still essential. Another disadvantage is that approximately 50% of malignant cases show only focal positivity, which significantly reduces its sensitivity because there may be only rare malignant cells present in a given biopsy.…”
mentioning
confidence: 99%